The story of hula - Golembe, Carla (Honolulu, Hawai'i Bess Press, 2004)
Tells the history of the hula, from modern hula as an entertainment, to ancient hula, which teaches the spiritual and cultural traditions of Hawai'i.
Performers on cd: Neolani K. Mahoe and Allison Chu.
Keywords: Hula (Dance) -- History -- Juvenile literature; Hawaii -- History -- Juvenile literature